PENICILLAMINE IN INTERSTITIAL LUNG DISEASE: A TIMELY REMAINDER OF AN OLD FOE - S, Pawadshettar; VK, ACHARYA; M, Arun; B, Unnikrishnan; Bv, Tantry (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Penicillamine-induced lung injury has been sparsely reported in the literature. We report one such case with its wide-ranging ramifications. We present an unusual case of drug induced-interstitial lung disease (DI-ILD) caused by penicillamine, resulting in acute lung injury in a young patient with Wilson's liver disease. Patient had a interstial lung disease which was attributed to the drug pencillamine. Penicillamine-induced lung injury has been sparsely reported in the literature and dose-dependent toxicity in a patient with neuro-psychiatric diseases adds to the rarity of the case. Furthermore, the complexities involved in diagnosing DI-ILD are deliberated. Keywords: Interstitial lung disease, Wilson's disease, Penicillamine.